Preliminary Stress Analysis of Aircraft Floor Support Structure Subjected to Emergency Landing Loads using Finite Element Method - Permana, Indra; Ikhsan, Muhammad; Setiajit, Sahid Bayu; Pratama, Riza Arif; Sriyanto, Sriyanto (Universitas Mercu Buana, 2022)
Floor support structure is a structural member of aircraft fuselage that have a function to support passenger and other payload loads inside the cabin. One type of load cases that should able to be carried on by floor support structures without permanent deformation is the emergency landing loads. This study aims to evaluate the strength of floor support structure of regional transport aircraft that consist of floor beams, seat tracks, and stanchions due to emergency landing loads. The study is carried on using Finite Element Method in MSC Patran/Nastran software. The structures are modeled using 1D element and the load is modeled as inertial loads given to the lumped mass of passenger and seat. The margin of safety is then calculated to evaluate the yielding of the structure material. The results show that in all cases the margin of safety is larger than zero which means that the structure is sill in elastic zone and there is no permanent deformation due to emergency landing load cases.